Potential Drivers of Adoption of Agronomic Practices: A Case of Beans Farmers in Uganda (London Journal of Research In Science: Natural and Formal, 2026)
This study aimed to identify the factors influencing the adoption of agronomic practices among bean farmers in Uganda, using secondary data from 1,908 farmers collected by the National Agricultural Research Organization (NARO). The analysis involved fitting multivariate probit and Poisson models to estimate the marginal effects of various determinants. The findings showed that 896 farmers adopted at least one agronomic practice, with mixed results in terms of direction and impact. Key positive determinants included marital status, education level, full-time farming, age, farming experience, farmer group membership, and credit access. Conversely, being male-headed, marital status, full-time farming, farm size, household size, and credit access were also identified as negative determinants. The study underscores the importance of socio-demographic and institutional factors in adopting agronomic practices and suggests integrating these insights into agricultural extension services. Further research is recommended to explore regional differences in adoption determinants across Uganda.
Keywords: adoption determinants; agricultural extension; agronomic practices; bean farmers; multivariate probit model; uganda